Why OECD Countries Should Reform Rules of Origin - Cadot, Olivier (World Bank, 2012)
With preferential trade agreements on the rise worldwide rules of origin—which are necessary to prevent trade deflection—are attracting increasing attention. At the same time, preference erosion for Generalized System of Preferences (GSP) recipients is increasing resistance to further multilateral negotiations. Drawing on different approaches, this article shows that the current system of rules of origin that is used by the European Union and the United States in preferential trade agreements (including the GSP) and that is similar to systems used by other Organisation for Economic Co-operation and Development countries should be drastically simplified if developed economies really want to help developing economies integrate into the world trading system. In addition to diverting resources for administrative tasks, current rules of origin carry significant compliance costs. More fundamentally, it is becoming increasingly clear that they are often been designed to force developing economies to buy inefficient intermediate products from developed economies to "pay for" preferential access for the final product. The evidence also suggests that a significant share of the rents associated with market access (net of rules of origin compliance costs) is captured by developed economies. Finally, the restrictiveness of rules of origin is found to be beyond the levels that would be justified to prevent trade deflection, suggesting a capture by special interest groups. The article outlines some alternative paths to reforms.